PENGARUH NUGET KILE (KELOR IKAN LELE) TERHADAP PENINGKATAN TINGGI BADAN BALITA STUNTING USIA 12-60 BULAN - Saadah Handayani (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2024)
Introduction: One of the health indicators evaluated by the Sustainable Development Goals (SDGs) in Indonesia is to reduce the stunting rate in Indonesia from 24.4% in 2021 to 21.6% in 2022. In Indonesia, there are many possible causes of stunting. Proximate factors, such as complementary feeding as well as related distal determinants, such as the food system. Most interventions to address stunting use fortified foods or supplements; however, there is little evidence on healthy locally available foods. Recommended local foods with high nutritional value are moringa and Clarias Gariepinus. Objective: To determine the effect of giving moringa leaf nuggets, Clarias Gariepinus on increasing the height of stunted toddlers aged 12-60 months. Methods: This type of research is a quasy experiment with a One group pretest posttest design. The study population was stunted toddlers at Paduraksa Health Center, Pemalang Regency aged between 12 to 60 months. 32 respondents were taken as random samples. Univarit analysis with central tendency and bivariate analysis with wilcoxon test. Results: on average there was an increase in height of 0.3 cm / toddler after the nuget kile intervention with a p value of 0.012, meaning that there was an effect of giving nuget kile (moringa Clarias Gariepinus leaves) on increasing the height of stunted toddlers aged 12-60 months.